1,1'-{2,2'-[1,4-Phenyl-enebis(methyl-ene)]bis-(-oxy)bis-(2,1-phenyl-ene)}diethanone - Al-Mohammed, N.N.; Alias, Y.; Abdullah, Z.; Khaledi, H. (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, C(24)H(22)O(4), contains one half-mol-ecule, the other half being generated by a crystallographic center of inversion. The central benzene ring makes a dihedral angle of 72.49 (5)° with the terminal benzene ring. In the crystal, adjacent mol-ecules are linked through C-H⋯O inter-actions, forming a sheet structure parallel to the bc plane. The sheets are stacked along the a axis via π-π inter-actions formed between the terminal benzene rings [centroid-centroid separation = 3.7276 (6) Å].